Control of fungal morphology for improved production of a novel antimicrobial alkaloid by marine-derived fungus Curvularia sp. IFB-Z10 under submerged fermentation. Issue 2 (February 2016) - Yang, Jun; Jiao, Rui-Hua; Yao, Ling-Yun; Han, Wen-Bo; Lu, Yan-Hua; Tan, Ren-Xiang
Graphical abstract: Highlights: Curvulamine production of IFB-Z10 was restricted by fungal morphology. Effects of medium components on fungal morphology are investigated. Effects of inoculum methods on fungal morphology and productivity are investigated. Talc powder addition further improved the curvulamine production. The highest production was obtained by addition of 5 g/L talc particles (200 mesh). Abstract: Curvulamine is a novel alkaloid with strong antimicrobial activity produced by the marine-derived fungus Curvularia sp. IFB-Z10. In this work, the effects of different carbon and nitrogen source on curvulamine production were firstly investigated. Different morphologies were formed and pellet-like growth of fungi was found positive for the curvulamine formation, and sucrose, yeast extract and sodium nitrate revealed most suitable for curvulamine formation. Subsequently, four seed culture methods were employed to examine the linkage between pellet shape and curvulamine production. The mean pellet diameter was significantly decreased and the production was improved to 17.97 mg/L by method M3, which used baffled shake flask and glass homogenizer to prepare the homogenized seed broth. Furthermore, microparticle-based morphology engineering was used to control the pellet shape and enhanced the curvulamine production. By supplementation of talc powder (200 mesh, 5 g/L), the mean pellet diameter dramatically decreased and the fermentation titer reached 33.05 mg/L, which was about 1.9-fold of the control (17.21 mg/L). In addition, the fermentation process was scaled up in a 5-L bioreactor and the curvulamine production reached 21.63 mg/L, which was about 3.3-fold of the control (6.58 mg/L). The results obtained provided a new approach to enhance curvulamine production.